TRENDS IN THE SCIENTIFIC LITERATURE ON THE LEAGILE SUPPLY CHAIN: BIBLIOMETRIC AND CITATION CONTEXT ANALYSES - Ton, Nguyen Trong Hien (Trường Đại học Đà Lạt, 2024)
Leagile is a hybrid of conventional lean and agile approaches intended to eliminate specific constraints and capacity limitations and enable agility in highly competitive business environments. Interest in incorporating lean and agile into the supply chain has grown in recent years, as shown by the growing number of scientific publications on this topic. This topic has garnered significant interest across a wide range of academic disciplines; however, a comprehensive study of the literature in this field has not yet been conducted. Therefore, the present study aims to provide a state-of-the-art summary of leagile supply chain issues that concern researchers. To do so, we use a bibliometric method, combined with citation context analysis, to evaluate data extracted from Scopus peer-reviewed articles published between 1999 and March 2023. Data analytic techniques, including citation analysis, co-citation analysis, and co-word (co-occurrence) analysis, are used. Using rigorous bibliometric and visualization tools, the results show the current status of the research problem, its impact, and suggestions for future work to address research gaps, such as a problem in an area of research that has been answered incompletely or insufficiently. The findings suggest that researchers in unexplored research areas in the ASEAN region include green supply chain strategies, supply chain risk management influenced by lean and agile strategies, and comparative analyses among ASEAN countries. These areas offer promising avenues for future research, contributing to regional competitiveness and performance enhancement.